Precocious Puberty with Primary Hypothyroidism due to Autoimmune Thyroiditis (Journal of Bangladesh College of Physicians and Surgeons, 2016)
Children with hypothyroidism generally have delayed pubertal development. Rare association with precocious puberty may occur especially in long standing untreated patients. The cardinal features of hypothyroidism induced pseudoprecocious pubertal development include thelarche, galactorrhoea & menarche . Other characteristic features are absence of sexual hair & retardation of linear growth. In this report a rare case of vaginal bleeding, large multicystic ovaries, precocious puberty, slow physical & mental growth in a seven and half years old girl with hypothyroidism due to autoimmune thyroiditis is described. It is important to recognize this syndrome because initiating simple thyroid hormone replacement completely resolves symptoms and hormone abnormalities, avoiding unnecessary investigations for malignancies or surgical intervention.J Bangladesh Coll Phys Surg 2016; 34(1): 45-47